Exploring the Geometric Principles of Javanese Tajug Houses: Enhancing Mathematics Education through Cultural Heritage - Hayuni, Argenti Agung; Ishartono, Naufal; Eko, Rizky Oktaviana; Waluyo, Mohamad (Universitas Sarjanawiyata Tamansiswa, 2025)
Many ethnomathematical studies focus on Indonesian culture, particularly traditional dwellings, although research into the mathematical notions of the Tajug House is sparse. There has been no previous research that examines the Tajug House form the aspect of geometry. Tajug houses are becoming increasingly rare. Nowadays students are less familiar with traditional house types. As a result, this study investigates the mathematical principles found in traditional Tajug houses in Java, and how these notions might be integrated into educational curriculum to conserve cultural heritage while also improving mathematics learning. This study used an ethnographic approach, to investigates the Tajug House's design through a literature review, expert interviews, and observations. The data obtained were analyzed based on mathematical and Tajug House knowledge by author to see the existence of mathematical concepts in the tajug house. The findings reveal significant geometric concepts, including plane geometry (square, triangle, trapezoid), solid geometry (cuboid), and geometric transformations (reflection). Square found in the base of the house, triangle found in the side of the roof, and trapezoid found in the base of pillar. Cuboid found in the pillar. Reflection found in the base of the house. These results suggest that Tajug Houses can effectively become one of the learning media to geometry subject in schools, demonstrating practical ethnomathematics applications. The learning process can utilize the GeoGebra application. By linking cultural heritage with mathematical education, this research promotes a deeper understanding of both subjects. Future studies should evaluate the effectiveness of Tajug House-based learning in improving students' math comprehension and cultural appreciation.